Queuing Rule of Thumb based on M/M/s Queuing Theory with Applications in Construction Management - Kardi Teknomo (Civil Engineering Dimension, 2012)
The current trend of queuing theory development is toward more precision which requires higher mathematical manipulation. In this paper, we attempted to reverve the current trend toward simplification of queuing formulas such that it can be used in more practical purposes, especially in construction industry. Through numerical examples of two case studies on concreting and earth moving, how to model the construction activities as queuing systems is illustrated systematically. Through the numerical examples, it is shown that when the customer cost is much lower than the server cost, queuing system can be simplified only to incorporate the constraint equation. The queueing constraint equation is suggested to be used as queuing rule of thumb. The proposed rule of thumb is rather conservative in term of queuing performance compared to the standard stochastic queuing formula because it is assumed that all the customers arrive at once in the beginning of the service.